Investigating the level of nurses’ participation in physicians’ clinical decisions and the factors affecting it: evidence from a cross-sectional study from nurses’ perspectives - Shima Bordbar; Maryam Radinmanesh; Jamshid Bahmaei; Hamidreza Farhadi Rad; Ali Reza Yusefi (BMC Health Services Research)
Abstract Background Interprofessional collaboration and participation of physicians and nurses in clinical decisions can be an important indicator in increasing the quality of safe care in hospitals. This study was conducted to investigate the level of nurses’ participation in physicians’ clinical decisions and the factors affecting it from the perspectives of nurses working in teaching hospitals affiliated with Shiraz University of Medical Sciences in southern Iran. Methods This descriptive-analytical cross-sectional study was conducted on 385 nurses from January to April 2024. The data collection tool was standard questionnaires. Data were analyzed using t-test, ANOVA, Pearson’s correlation coefficient, and multiple linear regression using SPSS23 software at a significance level of 0.05. Results The mean scores of nurses’ participation in physicians’ clinical decisions and the factors affecting this participation were 41.12 ± 6.57 out of 75 and 84.32 ± 8.16 out of 150, respectively, which indicated the moderate status of these two. Between the amount of nurses’ participation in physicians’ clinical decisions and factors affecting this participation, including individual factors (P < 0.001, r = 0.825), social factors (P < 0.001, r = 0.784), organizational factors (P < 0.001, r = 0.766), and clinical factors (P < 0.001, r = 0.759), a statistically significant correlation was observed. Furthermore, individual (β = 0.721; CI = 0.400–1.042), social (β = 0.691; CI = 0.395–0.987), organizational (β = 0.664; CI = 0.374–0.954), and clinical (β = 0.639; CI = 0.381–0.897) factors were found to be significantly associated with nurses’ participation in doctors’ clinical decisions (P < 0.001). In addition, age (β = 0.213; CI = 0.025–0.401) and work experience (β = 0.194; CI = 0.047–0.341) also showed significant associations with the outcome (P < 0.05). Conclusion Based on the results, the improvement of individual, social, organizational, and clinical factors may be associated with increasing nurses’ participation in physicians’ clinical decisions. It is recommended that nurses’ participation in clinical decisions be emphasized by holding ongoing training courses such as collaborative management, conflict management, and evidence-based decision-making for physicians. Hospital managers should also train and improve communication skills between physicians and nurses by holding periodic courses and seminars in hospitals. The findings of this study can be a basis for planning to improve the status of nurses’ participation in physicians’ clinical decisions in hospitals.